Effect of Quenching Process on Mechanical Properties of High Carbon Steels - Hande GÜLER (Uludağ University Journal of The Faculty of Engineering, 2014)
In this study, quenching process was applied to high carbon steel and the effect of this process on mechanical properties was investigated. The specimens were placed in a box-type furnace held at the desired temperature and then quenched. According to the tensile test and hardness measurements, it was concluded that the material has become brittle and the tensile strength decreased. The reason for this was higher cooling rate occurred during quenching process.